Mapping Trend of Digital Marketing Shapes Consumer Behaviour Across Indonesia: A Literature Review and Integration of Artificial Intelligence on Research Design for Future Research - Hermansyah, Hermansyah; Sihotang, Doni Sugianto; Ilhamilimy, Ridho Rafqi; Rizan, Mohamad; Wibowo, Setyo Ferry (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study presents a systematic literature review that maps the development of digital marketing research and its influence on consumer behavior across Indonesia, with an emphasis on the integration of Artificial Intelligence (AI) in future research design. Using content analysis on 60 journal articles published between 2012 and 2025, the study identifies five dominant variables—purchase decision, social media marketing, influencer marketing, brand trust, and brand image—alongside prevailing analytical methods, including Structural Equation Modeling (SEM) and Multiple Linear Regression. Bibliometric mapping through VOSviewer reveals clusters of thematic focus such as consumer engagement, digital branding, and e-commerce localization. The study also highlights trending topics over time, showing a shift from traditional marketing elements to AI-enhanced strategies. Furthermore, this paper proposes a conceptual framework linking AI applications with social media marketing, influencer marketing, and brand trust to guide future empirical studies. Findings underscore the growing academic and practical relevance of AI in digital marketing, and offer a foundation for predictive, data-driven approaches to understanding Indonesian consumer behavior.